Carbon Steel as the Potential Media for the Stringless Bee Tetragonula sp. Nest at Indralaya area in South Sumatra, Indonesia - Marisa, Hanifa (Journal of Applied Science, Engineering and Technology, 2021)
An investigation to observation the potential of stingless bee on building their nest at the high temperature material had been done to Tetragonula (Tetragona) sp. nest at Indralaya area, South Sumatra. Here we describe the Tetragonula sp nest that uses streetlight pole made by carbon steel as the nest media. Purposive sampling is used to select the target nest. Two streetlight poles found be used by Tetragonula sp as their home. The coordinate of location, height from ground surface, diameter of streetlight pole, air temperature and humidity, and floral species around nest, were noted. The spot coordinate of the area is between S 30 14’ 19.2498’’ and E 1040 39’ 15,3288’’ at 1,5 m above the ground surface with 12 cm diameter of pole and the highest air temperature was 350C at daylight during the months of sampling with about 80 – 90 % humidity. Some floral ; which Switenia macrophyla, Hevea brasiliensis, Zea mays, and Citrullus lanatus floral species are planted around. Air temperature in the pole is very high, around 400 C during daylight.